Self-report of parenting style, socio-economics status and psychological functioning in a community sample of 13-15-year-old students - Ritchie, C; Buchanan, A (SAGE Publications, 2010)
Summary: Data from 391 students aged 13-15 were analysed using bivariate analysis to determine the extent to which student self-report of 'negative' parenting styles was associated with psychological functioning, as defined by the Strengths and Difficulties Questionnaire (SDQ) (Goodman, 1997) and with self-report of socio-economic status. Findings: The findings affirm that children who perceived parenting styles as negative are more at risk of abnormal psychological functioning as measured by the SDQ, and that perhaps contrary to expectations, the children of those from professional backgrounds may be at greater risk of perceiving parenting as negative and of poor psychological functioning than those from low income backgrounds. Applications: It is concluded that 'risk' to children, while present in negative parenting, is exacerbated by wider factors in the ecological framewok such as school, housing, income, and aspirations, and that social work and policy initiatives aimed at parenting and at low income families are unlikely to be successful in producing well adjusted young people without much greater investment in the wider fabric of their lives.